2020
DOI: 10.1007/s10551-019-04416-0
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Environmentally and Socially Responsible Sustainable Consumer Behavior

Abstract: Responsible sustainable consumer behavior (RSCB) involves a complex pattern of environmental and social issues, in line with the view of sustainability as a construct with both environmental and social pillar. So far, environmental dimension was far more researched than social dimension. In this article, we investigate the antecedents of both environmentally and socially RSCB and willingness to behave in environmentally/socially responsible way. We include measures of concern, perceived consumer control/effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
146
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(194 citation statements)
references
References 63 publications
(102 reference statements)
9
146
0
5
Order By: Relevance
“…The choice of constructs in our study was guided by the research of Brochado et al (2017), who found that the individual or psychographic factors were more relevant than demographic variables. For example, environmental concern was found to be one of the factors with the strongest impact on environmental behavior in a recent study by Hosta and Zabkar (2020). What is more, Kang et al (2013) led us to the trio of individual factors, i.e.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The choice of constructs in our study was guided by the research of Brochado et al (2017), who found that the individual or psychographic factors were more relevant than demographic variables. For example, environmental concern was found to be one of the factors with the strongest impact on environmental behavior in a recent study by Hosta and Zabkar (2020). What is more, Kang et al (2013) led us to the trio of individual factors, i.e.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…They were told that for a specific variety of apples, there were two options, namely, local apples costing 10 Subjects were asked to choose between the local or imported apples or select neither. After making a choice, respondents completed a five-item scale of personal norms (Hosta and Zabkar, 2020), adapted to local foods (a = 0.893). In addition, to further enhance understanding of choices, respondents completed the five-item scale of Lichtenstein et al (1993) to capture price consciousness (a = 0.902).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Studies clearly present the role of attitudes, values, beliefs, knowledge, personality and skills in explaining environmental behavior (Biswas and Roy, 2015;Obery and Bangert, 2017). Other constructs like collective efficacy (Chen, 2015;Neamtu et al, 2014), emotions (Rees et al, 2015), mindfulness (Panno et al, 2018), environmental consciousness (Garvey and Bolton, 2017), perceived behavioral control (Hosta and Zabkar, 2020) and social influence (Axsen and Kurani, 2014) are also shown to be related to proenvironmental behavior. Oreg and Katz-Gerro (2006) developed one of the most comprehensive cross-national proenvironmental behavior models and one of the few not to be limited to either a local or single-country context or one specific proenvironmental behavior.…”
Section: Introductionmentioning
confidence: 98%